Antimicrobial silver nanoparticle-photodeposited fabrics for SARS-CoV-2 destruction - Kumar, Aditya; Nath, Kalpita; Parekh, Yash; Enayathullah, M. Ghalib; Bokara, Kiran Kumar; Sinhamahapatra, Apruba (Colloid and interface science communications, 2021)
Surfaces containing antiviral nanoparticles could play a crucial role in minimizing the virus spread further, specifically for COVID-19. Here in, we have developed a facile and durable antiviral and antimicrobial fabric containing photodeposited silver nanoparticles. Scanning and transmission electron microscopy, UV-VIS spectroscopy, and XPS are used to characterize the silver nanoparticles deposited cloth. It is evident that Ag0/Ag+ redox couple is formed during fabrication, which acts as an active agent. Antiviral testing results show that silver nanoparticles deposited fabric exhibits 97% viral reduction specific to SARS-CoV-2. Besides its excellent antiviral property, the modified fabric also offers antimicrobial efficiency when tested with the airborne human pathogenic bacteria Escherichia coli and fungi Aspergillus Niger. The direct photodeposition provides Ag-O-C interaction leads to firmly grafted nanoparticles on fabric allow the modified fabric to sustain the laundry durability test. The straightforward strategy to prepare an efficient antimicrobial cloth can attract rapid large-scale industrial production. [Display omitted] •Photodeposition of ~10 nm silver nanoparticles on the fabric under UV irradiation•Ag0/Ag+ redox couple confirmed by TEM, SEM, XPS, UV-VIS•Washing durable up to 5 times•The fabric offers anti-microbial properties•The fabric exhibits 97% viral annihilation specific to SARS-CoV-2